Truncated AUC in the Evaluation of Fluconazole Bioequivalence - Portolés, Antonio; Almeida, Susana; Terleira, Ana; Pablo, Itziar de; Filipe, Augusto; Caturla, Maria Cruz; Moreno, Alfonso (Arzneimittelforschung, 2004)
The bioequivalence of two capsule formulations (test and reference) containing 200 mg fluconazole (CAS 86386-73-4) was assessed in 24 healthy volunteers in an open, randomised, crossover, 2 periods × 2 sequences single dose study with a minimum washout period of 14 days. Plasma samples were obtained over 168 h (at baseline, 1 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 5 h, 6 h, 8 h, 12 h, 24 h, 48 h, 72 h, 120 h and 168 h after administration) and fluconazole concentrations were determined by means of an HPLC-UV method (limit of quantification: 0.2 µg/mL). Pharmacokinetic parameters used for bioequivalence assessment (AUClast, AUCinf and Cmax) were determined from the fluconazole concentration data using non-compartmental analysis. The results showed that all 90 % confidence intervals (obtained by ANOVA) were 100.89-110.24 for Cmax, 99.07-107.35 for AUClast and 95.42-105.17 for AUCinf, that is, all within the predefined ranges. Furthermore AUCs truncated at 24, 48, 72 and 120 h were also within the 80-125 % range. It may be therefore concluded that the evaluated formulations are bioequivalent in terms of rate and extent of absorption.
Keywords: Antifungal agent; CAS 86386-73-4; Fluconazole, area under the curve, bioequivalence, truncated AUC